An investigation into the historical context of graves exhumed on the farm Wemmershuis 379JT, Belfast - Anton C. van Vollenhoven (Contree)
The South African National Road Agency Limited (SANRAL) requested Archaetnos to exhume historical graves on the farm Wemmershuis 379JT in the Belfast district, Mpumalanga Province, as the upgrade to the R33 road was impacting on the graves. The human remains were reinterred on the same farm, to another part of the semi-formal graveyard. A monument commemorating the deceased was also erected.